Collaboration, knowledge and innovation toward a welfare society: the case of the Board of Social Farming in Valdera (Tuscany), Italy. Issue 4 (8th August 2017) - Di Iacovo, Francesco; Moruzzo, Roberta; Rossignoli, Cristiano M.
ABSTRACT: Purpose : Through an analysis of a social farming (SF) case study, this article investigates how collaboration and knowledge co-creation between different actors can support the process of rural transition in order to stimulate innovation in the welfare system using agricultural resources. Methodology : We used the 'Antecedent-Process-Outcome Framework' developed by Wood and Gray [1991. "Toward a Comprehensive Theory of Collaboration." The Journal of Applied Behavioral Science 27 (2): 139-162] and adapted by Thomson and Perry [2006. "Collaboration Processes: Inside the Black Box." Public Administration Review 66 (s1): 20-32], to analyse the collaborative process within the Board of Social Farming (BSF) in Valdera, Italy. The BSF in Valdera is particularly important as it was the first transition arena developed in Italy for SF development. Findings : The article highlights the difficulties and opportunities encountered by the BSF in the knowledge co-creation and collaboration, and identifies key elements to facilitate innovation in SF and more generally in transition processes. Practical implications : The article aims to generalize crucial practical elements in the relationship between collaborative approaches and innovation in the field of innovative welfare society, which is increasingly key to rural transition. Theoretical implications : Innovation in SF is complex due to the need to identify new knowledge, diverse kinds of organizations and innovative interactions among many private and public stakeholders. The article explores the concept of collaboration in SF in order to re-define the production of public and private goods within local and rural communities. Originality : The article aims to contribute to the ongoing discussion on the advantages and disadvantages of collaboration in order to reinforce rural transition pathways.